2020
DOI: 10.1155/2020/9075165
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy Facilitates Reference Gene Selection by RT-qPCR Analysis in Kidney Yang Deficiency Syndrome Mice Infected with the Influenza A (H1N1) Virus

Abstract: In reverse transcription-quantitative polymerase chain reaction (RT-qPCR) studies, endogenous reference genes are routinely used to normalize the expression of target gene studies. In order to precisely evaluate the relative expression of genes in the cells of mice suffering from Kidney Yang Deficiency Syndrome (KYDS) in response to influenza A virus (IAV) H1N1 using RT-qPCR, it is crucial to identify reliable reference genes. In the present study, 15 candidate reference genes (Actb, β2m, Gapdh, Gusb, Tuba, Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Being excluded from the analyses in the filtration steps, Rpl32 was not identified as a suitable HKG in the current work for neither lung tissue nor other tissues. The results of Fu et al (2020) indicated that none of the 15 WU-HKGs that they studied were sufficiently good as reference genes. However, they suggested the combination of Grcc10 and Ppia genes as a proper choice for the lung tissue of mouse infected with IAV.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Being excluded from the analyses in the filtration steps, Rpl32 was not identified as a suitable HKG in the current work for neither lung tissue nor other tissues. The results of Fu et al (2020) indicated that none of the 15 WU-HKGs that they studied were sufficiently good as reference genes. However, they suggested the combination of Grcc10 and Ppia genes as a proper choice for the lung tissue of mouse infected with IAV.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have reported relatively high variability for the expression of WU-HKGs in a varied range of tissues and organs in livestock animals ( Gromboni et al, 2020 ; Lozano-Villegas et al, 2021 ) as well as in humans ( Mahoney et al, 2004 ; Caracausi et al, 2017 ; Cadenas et al, 2022 ), mice ( Fu et al, 2020 ; Muñoz et al, 2021 ), and insects ( Shi et al, 2016 ), among others.…”
Section: Resultsmentioning
confidence: 99%
“…All possible pairs of DEirlncRNAs (denoted lncRNA-A and lncRNA-B, respectively) were identified and assessed based on the following definitions: (I) if the ratio of lncRNA-A expression to lncRNA-B expression was greater than 1, the pair was defined as lncRNA-A|lncRNA-B = 1; (II) if the ratio of lncRNA-A expression to lncRNA-B expression was less than 1, the pair was defined as lncRNA-A|lncRNA-B = 0; (III) for a given pair, if lncRNA-A|lncRNA-B = 1 in more than 80% of all patients, the pair was considered invalid; and (IV) if lncRNA-A|lncRNA-B = 0 in more than 80% of all patients, the pair was also considered invalid. [ 21 ] Valid DEirlncRNA pairs were identified by applying these definitions and used to construct a matrix with each entry corresponding to the value of the respective lncRNA-A|lncRNA-B. Combining clinical survival status and survival time data from TCGA, prognostic DEirlncRNA pairs were obtained by univariate Cox regression analysis and least absolute shrinkage and selection operator (LASSO) regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 , 20 ] Compared to multiple gene combinations, two-gene combination strategy can provide relative expression within a sample, leading to more robust and accurate speculation. [ 11 , 21 , 22 ] At the same time, the relative expression of gene pairs takes into account all possible combinations. [ 23 ] Therefore, developing new irlncRNAs to treat melanoma is of great significance and could improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation